Effectiveness of the E-SAKIP Application in Monitoring and Evaluating Performance at the Surabaya High Religious Court - Muhammad, Nur Sa'adah; Hermawan, Sigit; Abadiyah, Rifdah (International Journal of Economics Development Research (IJEDR), 2024)
Accountability and transparency are essential requirements for public institutions to gain public trust, which can be achieved through the implementation of e-government initiatives such as the electronic Government Agency Performance Accountability System (e-SAKIP). Although e-SAKIP aims to facilitate the monitoring, evaluation, and reporting of government agency performance, its implementation still faces several technical and human resource challenges that need to be addressed to achieve optimal effectiveness. This research aims to analyze the causes of ineffectiveness and inhibiting factors in the use of the e-SAKIP application, as well as examine efforts to improve its effectiveness in monitoring and evaluating performance at the Surabaya Religious High Court. This study uses a descriptive qualitative method with primary data from structured and in-depth interviews with informants selected through purposive sampling, as well as secondary data from related documents. Data analysis uses thematic analysis techniques with source and method triangulation to enhance validity. The research results at the Surabaya Religious High Court show that the implementation of the e-SAKIP application faces various challenges that hinder its effectiveness. The main issues include feature incompatibility, technical and infrastructure constraints, lack of training, data accuracy problems, coordination difficulties, increased workload, and concerns related to system transparency and sustainability. To address these issues, comprehensive efforts are needed, including feature adjustments, infrastructure improvements, continuous training, enhancing data accuracy, optimizing coordination and workload, and implementing effective change management. The implementation of these measures is expected to improve the effectiveness of e-SAKIP in enhancing overall institutional performance.